(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad and his pure and pure family and companions, and those who followed them in goodness until the Day of Judgment.And yet:The considered sciences vary in status from honorable to the most honorable according to that known, and there is no doubt that the highest status and the most reliable handhold is what is connected to the Great Book of God.And the first science related to this holy book was the science of interpretation, through which he could come to know what God intended in His speech and judgment for His servants.This noble book has two ways of interpreting it and apprehending its meanings, and there is no third for them. Either the word should be interpreted with an idiomatic legal interpretation, i.e. the Lawgiver conveys it to a meaning other than what it was put for in the language, or it should be left on what is known to it of its positive meaning in the Arabic language, and the context of the speech is Which will determine one of the concerned, for example, the word (prayer), as it came mostly in its idiomatic meaning, which is the well-known worship, but we find it in other places that it came in its linguistic meaning, which is supplication, such as the Almighty’s saying  ﮡ ﮢﮣ ﮤ ﮥ ﮦ ﮧ  al-Tawbah: 103.And from what we have mentioned above, it appears that whoever wants to understand the word of God Almighty, he must know what is narrated in the interpretation of the Qur’an, and what remains on its linguistic origin. Peace and blessings be upon him) and the Companions and the Followers (may God be pleased with them), so we see that the Companions at the beginning did not ask the Prophet about all of the Qur’an, but rather they asked him about what was most accurate in his understanding, because it was revealed in their language, so Abu Bakr, may God be pleased with him, for example, understood the Qur’an as Abu Lahab understood it, but he There is a difference between a slave who did what he understood to surrender himself to his innocence, who was keen to save him from himself, and another who delivered him what he understood to destroy himself in obstinacy and disbelief.